Ultrasound of Abdomen in Dengue Hemorrhagic Fever: Case Study - Nursama Heru; Puji Supriyono; Halimatus Sa’diah; Ade Rochimat (Poltekita : Jurnal Ilmu Kesehatan, 2023)
The objective of study to evaluate technical scanning and Image result of dengue haemorragic fever (DHF) on abdominal ultrasound examination. The Methods was a case study Presentation from 3 patients, and observations were taken from March 2022 to July 2022 at the RSUD Cengkareng Jakarta. Using a 3.5 MHz frequency convex transducer, take longitudinal and transverse shots with the supine patient position. Scanning focuses on the peritoneal cavity to evaluate the presence of plasma fluid that fills the peritoneal cavities. The results showed that the abdominal ultrasound examination procedure with clinical DHF was well done with patient preparation not eating fibrous at least 4 hours, drinking 3-4 glasses of water and holding urination about 2 hours to fill the bladder. The results show that there is fluid in the peritoneal cavity